2003
DOI: 10.1128/jcm.41.6.2330-2336.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Ampicillin-Resistant Enterococcus faecium Isolates from Hospitalized Patients in Norway

Abstract: The genetic relationship of 81 ampicillin-resistant and 21 ampicillin-susceptible Enterococcus faecium isolates from clinical infections and rectal screening in hospitalized patients in Norway was studied by pulsedfield gel electrophoresis (PFGE) and amplified fragment length polymorphism (AFLP). PFGE showed 55 different banding patterns, and 65 of the isolates could be grouped into one large group. With AFLP, 46 patterns were discerned, and 74 isolates clustered in one group. In general, the isolates had a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
33
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 37 publications
9
33
1
Order By: Relevance
“…Amoxicillin resistance in E. faecium was significantly higher and this finding is similar to the report of Jureen et al(2003) 18 . According to their study this kind of resistance in Enterococci may be due to the production of low-affinity penicillin-binding protein.…”
Section: Resultssupporting
confidence: 81%
“…Amoxicillin resistance in E. faecium was significantly higher and this finding is similar to the report of Jureen et al(2003) 18 . According to their study this kind of resistance in Enterococci may be due to the production of low-affinity penicillin-binding protein.…”
Section: Resultssupporting
confidence: 81%
“…Torell et al (55) described a clonal subset of Swedish vancomycin-susceptible Amp r E. faecium strains with high-level ciprofloxacin resistance and mutations in the QRDR genotyped by biochemical fingerprinting (PhenePlate). In addition, Jureen et al (25), showed a correlation between ampicillin and ciprofloxacin resistance among genetically highly similar Norwegian isolates that also carried the purK-1 allele, indicative for CC17. More specifically, Mohn et al (38) identified fluoroquinolone prescription as a risk factor for fecal carriage with an outbreak of ampicillin-resistant E. faecium in a Norwegian hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This subpopulation belongs to a distinct genetic lineage labeled clonal complex 17 (CC17) (62) and is associated with the presence of the variant esp gene as part of a pathogenicity island (31) and resistance to ampicillin. Recently, resistance to ciprofloxacin appeared to be associated with ampicillin resistance in genotypically related E. faecium isolates from Norway (25,55,56) and Spain (7).To substantiate a common genetic background of quinoloneresistant E. faecium and association with the hospital-adapted CC17, we studied the genetic relatedness of 32 ciprofloxacinresistant and 31 ciprofloxacin-susceptible E. faecium isolates from various human and animal origins by multilocus sequence typing (MLST) and determined susceptibility to vancomycin and ampicillin and the presence of esp. Finally, we sequenced the quinolone resistance-determining regions (QRDR) of parC and gyrA to identify mutations involved in ciprofloxacin resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Emergence of ampicillin resistance in E. faecium in the United States in the early 1980s preceded the rapid increase of vancomycin resistance (10,18,20). Nowadays, VREF is endemic in many hospitals in the United States, and prevalence rates in European hospitals are rising, with VRE rates above 10% in at least six European countries (3,4,9,15,26,32; Annual report of the European Antimicrobial Resistance Surveillance System, 2002 [www.earss.rivm.nl]).…”
mentioning
confidence: 99%